Sulfur dioxide response of Brettanomyces bruxellensis strains isolated from Greek wine. (April 2019) - Dimopoulou, Maria; Hatzikamari, Magdalini; Masneuf-Pomarede, Isabelle; Albertin, Warren
Abstract: Brettanomyces bruxellensis is the most common spoilage wine yeast which can provoke great economic damage to the wine industry due to the production of undesirable odors. The capacity of the species to adapt in various environmental conditions offers a selective advantage that is reflected by intraspecific variability at genotypic and phenotypic level. In this study, microsatellite analysis of 22 strains isolated from Greek wine revealed the existence of distinct genetic subgroups that are correlated with their geographical origin. The response of these strains to increasing levels of sulfur dioxide confirmed the presence of both sensitive and tolerant strains, which belong to distinguished genetic clusters. The genetic categorization of B. bruxellensis strains could be used by the winemakers as a diagnostic tool regarding sulfur dioxide sensitivity. Highlights: B.bruxellensis population is structured according to isolation matrix and geographical origin. The strains isolated from sweet wine were more tolerant to sulfur dioxide than the strains isolated from dry wine. Isolates from the same genetic cluster showed similar response to sulfur dioxide.